Juvenile Delinquency and Its Effects on Students Mental Health and Academic Performance in Nigeria - Maureen Chinasa Ola-Williams; Adeyinka Ola-Williams; Clement Aliu Ogbaini (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Juvenile delinquency is a significant problem in all societies around the world, including Nigeria, where it has implications for student mental health and academic performance. This study investigates the relationship between juvenile delinquency and its impact on the mental health and academic performance of students in Nigeria. The study was designed to identify the prevalent forms of juvenile delinquency, the underlying factors contributing to these behaviours, and the effects on student's mental health and educational outcomes. A cross-sectional research design was adopted and a sample of 250 students from ten public secondary schools in Mushin Local Government Area of Lagos State was chosen for the study. The findings reveal a significant relationship between juvenile delinquency and student mental health, with higher rates of stress, anxiety, and depression among affected students. Additionally, the findings revealed a significant impact of juvenile delinquency on academic performance, as it negatively influenced students' ability to learn, concentrate, and achieve educational goals. The prevalence of juvenile delinquency was also found to vary across different socio-economic backgrounds. The study concluded with recommendations for the implementation of comprehensive intervention strategies, including counselling services, community-based programs, and policy changes, to address the needs of students affected by juvenile delinquency in Nigeria.